The effect of digitonin on egg quality, cholesterol content in eggs, biochemical and haematological parameters in laying hens - E. Tůmová; H. Härtlová; Z. Ledvinka; A. Fučíková (Czech Journal of Animal Science, 2004)
The aim of the present study was to describe the effect of digitonin on egg quality, cholesterol content in eggs, some parameters of serum lipid metabolism and blood picture of laying hens. The experiment was split into 3 groups (8 laying hens per group); group 1 was fed control feed mixture with 16.54% crude protein and 11.61 MJ ME, group 2 received control feed mixture with 0.01% digitonin and supplement of digitonin in group 3 was 0.025%. Digitonin in the amount 0.025% significantly (P≤ 0.05) reduced egg weight from 65.07 g in control group to 61.44 g in group 3, white weight (41.21 g vs. 37.96 g), and egg cholesterol content (13.64 mg/g vs. 12.95 mg/g of yolk). Digitonin significantly (P ≤ 0.05) increaced HDL cholesterol (0.43 mmol/l in control group to 0.59 mmol/l in group 3) and triglycerides from 13.47 mmol/l (control) to 16.90 mmol/l (group 3) in blood serum. Significantly (P ≤ 0.05) lower number of erythrocytes and MCV value in group 3 were observed.